Mathematical Modeling of Roof Solar Chimney for Small Scale Power Generation - Al-Kayiem, Hussain H. (UNIMAS, 2008)
The OnRoof Solar Chimney is a simple technique for smallscale utilization of solar energy. In this paper, a mathematical model is developed to describe the thermofluid behavior of the air in the chimney. A smallscale experimental model with adjustable roof angle was built and was used to perform measurements to study the effects of roof angle and also daylong performance of the model. The experimental study showed an adequate temperature rise in the system and validated the potential to generate enough air flow to operate a Savonius wind rotor to produce electricity. The highest measured temperature for the collector surface and the chimney exit were 97°C and 57.4°C, respectively. Computations were performed based on mixed convection heat transfer mode inside the collector. The calculated power that could be produced for a building of 10m x 20m at base roof area was1.36 kW, which demonstrated the feasibility of using OnRoof Solar Chimney to generate power for medium sized buildings such as dormitories, schools, and public halls